Bahraini Females Knowledge about Developmental Delay in Children: A Cross Sectional Study - Abdulla M. Rabeah, Mohamed K. Fadhul, Amer Kamal*, Omar Y. Alkhajah, Abdulla A. Khaled, Abdulla A. Almahmood, Abdulla M. Alsubaiee (Innovative Journal of Medical and Health Sciences, 2019)
Guidelines for normal child development had been constructed by studying patterns of growth and development. They included physical, socio-emotional, cognitive and motor development in relation to age. The aim of this study was to provide a statistical data regarding knowledge of milestones in Bahraini females and their awareness of delayed milestones complication. This cross-sectional study was conducted from the period of 6th of November 2018 until January 2019. Bahraini females older than 18 years of age (n=628) were selected randomly. Each participant had to fill a specific questionnaire which included questions to identify the level of knowledge about the milestones and if they are able to identify abnormal behavior. The results showed that 93.94% of the population has failed to answer 53% of the survey correctly, leaving only 6.06% of the population completing the survey with correct answers exceeding the cut-off point. This exhibited the lack of knowledge towards developmental milestones and the complications that arise due to their delay. We concluded that Bahraini females lack the knowledge of developmental milestones and the complications of this lack on early detection of diseases in their babies. This showed that developmental milestones were mistakenly not taken seriously and were underestimated. Keywords Bahraini females, Knowledge, Developmental delay, Cross-sectional study, Milestones.